Bullous Hemorrhagic Dermatosis Induced by Enoxaparin: About a Case in Madagascar - Fenohasina Rakotonandrasana; Fandresena Arilala Sendrasoa; Andrianandrianina Mbolatiana Kiady Armando Rakotomanana; Herin’Ny Fitiavana Princia Andriatahina; Voahanginirina Nathalie Ralimalala; Samson Léophonte Ramily; Moril Sata; Onivola Raharolahy; Malalaniaina Andrianarison; Irina Mamisoa Ranaivo; Lala Soavina Ramarozatovo; Fahafahantsoa Rapelanoro Rabenja (Case Reports in Dermatological Medicine, 2023)
Bullous hemorrhagic dermatosis is an adverse reaction occurring within 5 to 21 days after anticoagulation; the diagnosis is to be evoked in the presence of hemorrhagic bullous lesions at a distance from the injection site in the days following the introduction of anticoagulant; this is a diagnosis of exclusion. It is a rare pathology that mainly affects the elderly. A 54-year-old man presented with bullous hemorrhagic lesions on the left upper limb starting at the 4th day after enoxaparin injection, diagnosed as a bullous hemorrhagic dermatosis induced by enoxaparin. We report the first case of bullous hemorrhagic dermatosis induced by enoxaparin in Madagascar.